2021
DOI: 10.3390/ijms22041760
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Restores Skeletal Muscle Cell Remodeling and Myogenic Program: Potential Impact on Human Health

Abstract: Skeletal muscle cells, albeit classified as vitamin D receptor (VDR)-poor cells, are finely controlled by vitamin D through genomic and non-genomic mechanisms. Skeletal muscle constantly undergoes cell remodeling, a complex system under multilevel regulation, mainly orchestrated by the satellite niche in response to a variety of stimuli. Cell remodeling is not limited to satisfy reparative and hypertrophic needs, but, through myocyte transcriptome/proteome renewal, it warrants the adaptations necessary to main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 97 publications
(133 reference statements)
0
6
0
Order By: Relevance
“…Moreover, tissue repair is supported by various nutritional factors. For example, a low level of vitamin D has been associated with maladaptation of skeletal muscle and bone tissue [ 42 ]. Proper muscle renewal in response to exercise is required for optimal hypertrophic effects [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, tissue repair is supported by various nutritional factors. For example, a low level of vitamin D has been associated with maladaptation of skeletal muscle and bone tissue [ 42 ]. Proper muscle renewal in response to exercise is required for optimal hypertrophic effects [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, tissue repair is supported by various nutritional factors. For example, a low level of vitamin D has been associated with maladaptation of skeletal muscle and bone tissue [42].…”
Section: Injury and Nutritionmentioning
confidence: 99%
“…Indeed, general important concerns still exist in several aspects, including the lack of a clear indication of the optimal dose requirement to respond to extra-skeletal needs, or the lack of a clear definition of vitamin D insufficiency/deficiency, based on well-defined serum ranges (still missing as well) [ 151 , 152 , 153 ]. Data from trials on D hormone supplementation, either alone or combined, are unsatisfactory likely due to the high variability in protocols and heterogeneity of the studied populations, since general health status, ethnicity, sedentary habit are often not defined, as recently summarized elsewhere [ 80 , 81 ]. Furthermore, recent evidence highlights the major role of exercise-induced sex-dependent heart remodeling during life of men and women at different ages, either sedentary or physically active [ 129 ].…”
Section: Discussionmentioning
confidence: 99%
“…It should be kept in mind that vitamin D is a molecule with quite a special identity, presenting features typical of a nutrient, a hormone and a rapid regulating factor; it is able to affect human health through a fine-tuned regulation of cell functions, by actively participating in biomolecule networking, as recently reported [ 80 , 81 , 82 ].…”
Section: Cardiovascular Health Beyond Sex Hormones: Vitamin D Mattersmentioning
confidence: 97%
“… 14 , 15 Studies have shown that VDR plays an important role in cardiovascular and neurodegenerative diseases, skeletal muscle cell remodeling, muscle regeneration, and inflammatory bowel disease. 16 , 17 In addition, VDR has a protective effect on the kidneys. 18 There is a relative lack of VDR in some kidney-related diseases such as glomerulonephritis, acute kidney injury, and DKD.…”
Section: Introductionmentioning
confidence: 99%